Open Innovation In Marketing Research: A Bibliometric Review Of Conceptual and Empirical Developments - Joval Ifghaniyafi Farras; Lina Maryana (CV Putra Publisher, 2026)
Open innovation (OI), defined as the purposive management of knowledge inflows and outflows to accelerate innovation, has become an increasingly prominent framework in marketing scholarship as markets digitize and value creation shifts toward interactive ecosystems. Despite this growing interest, marketing oriented OI research remains conceptually dispersed across adjacent constructs such as co creation, customer engagement, user innovation, social media enabled collaboration, and platform mediated communities. This study provides a bibliometric review that maps the conceptual and empirical development of OI in marketing research through an analysis of keyword co occurrence patterns and thematic evolution. Following established bibliometric guidelines, the domain is synthesized using VOSviewer science mapping techniques, including network, overlay, and density visualizations. The resulting network structure positions open innovation as a central hub connected to three dominant thematic areas. These include co creation and new product development, frequently examined in SME and Industry 4.0 contexts; digital and social media enabled engagement and prosumption; and value co creation and interactive marketing within customer communities and networked organizational forms.